VD_FINDINFO ML / 2013 / 337 vom 4. Dezember 2013 - VD Tribunal cantonal (2013)
DÉPENS, AGENT D'AFFAIRES, DISPROPORTION, VALEUR LITIGIEUSE | 105 al. 2 CPC (CH), 106 al. 1 CPC (CH), 95 al. 1 CPC (CH), 95 al. 3 let. b CPC (CH), 11 TDC, 20 al. 2 TDC, 3 TDC